A cowboy of legend - Broday, Linda (Broday, Linda Lone Star legends, 2021)
"Deacon Brannock is determined to make a name for himself and the saloon he's worked his whole life to afford. He was prepared for life in the Wild West, but he hadn't counted on Grace Legend... Grace has always fought hard for what she believes in, and after her best friend is killed at the hands of her drunk and angry husband, that includes keeping alcohol out of her town. When the owner of the new saloon turns out to be a kind and considerate man, she can't help but wonder if they could have a future together...if they weren't on opposite sides of every issue."--Provided by publisher.